(3LhGeY GdEScfOQGfjjf dcJGH LGdjfhS aj Gdbhi GdWHjYjIs - (3LGdjfhSs
(3ChdgG (B:s
(3Gdbhi KdGKI CLfGS , aefgG faSGfjI , hefgG MjhGfjI , hefgG WHjYjI, hGdbhi GdfaSGfjI KdGKI CfhGY, aefgG MSjI hefgG MQcjI , hefgG SjGSjI s
(3BNQgG (B:s
(3GdTQGH jfaP SQjYkG hjOQ GdHhd hGdQGHYI Cf Jchf GdbhI GdMGOKI bhJg s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B76 s
(3eUOQ GbJfGA GdCUd (B:s
(3CjGUhajG (B(3588) s
Keywords: (3GdWHs